Preparation method of porous lithium titanate ceramic spheres based on nanowire construction

Through the preparation method of porous lithium titanate ceramic spheres based on nanowires, the problems of organic residue and pore regulation in the prior art are solved, and high-efficiency tritium release and mechanical strength are achieved. The tritium proliferation agent suitable for lithium ceramics are suitable for lithium ceramics. .

CN116903362BActive Publication Date: 2025-01-14XIAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310334168.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-01-14
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

The existing methods for preparing porous ceramic materials require the use of organic porous agents or foaming agents, which leads to by-product residues and is difficult to effectively regulate porosity and pore size, affecting the tritium release performance and mechanical strength of lithium ceramics.

Method used

The preparation method of porous lithium titanate ceramic spheres constructed based on nanowires is adopted to prepare α-lithium titanate nanowires by hydrothermal method to form β-lithium titanate ceramic spheres with porous structures, avoid the use of organic pore-forming agents, and use The sintering process controls the porosity and pore size to ensure that the ceramic maintains good compression strength at high porosity.

Benefits of technology

The preparation of porous ceramics with green and environmental protection is realized, which avoids organic matter residues, regulates the pore structure, improves the tritium release efficiency and the mechanical strength of the ceramics, and alleviates the hardening problems caused by radiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116903362B_ABST
    Figure CN116903362B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing porous lithium titanate ceramic spheres based on nanowire construction, which is specifically implemented according to the following steps: step 1, preparing α-lithium titanate nanowires by a hydrothermal method; step 2, preparing lithium ceramic microsphere green body; step 3, preparing porous structure β-lithium titanate ceramic spheres. The present invention utilizes the characteristics of lithium titanate nanowires to construct a porous structure, controls the porosity and pore size by controlling the sintering process, and avoids the use of organic pore formers or other additives; at the same time, the structure of the nanowires overlapping each other can also ensure that the ceramics still maintain good compressive strength at high porosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tritium breeding materials, and in particular relates to a method for preparing porous lithium titanate ceramic spheres based on nanowire construction. Background Art

[0002] As the core functional material of the breeder blanket in nuclear fusion reactors, lithium ceramics undertake the important functions of tritium production and energy exchange. Li2TiO3 ceramics have become one of the preferred materials for solid tritium breeders due to its excellent chemical stability, high melting point, high mechanical strength, and low tritium release temperature.

[0003] Studies have shown that increasing the porosity (especially the open porosity) can significantly improve the tritium release performance of lithium ceramics and increase the tritium release efficiency. At the same time, the pores as free surfaces are conducive to reducing the accumulation of irradiation point defects and alleviating the swelling and hardening of lithium ceramics. Therefore, the pore structure design of lithium ceramics is crucial to the development of advanced solid-state tritium breeding materials.

[0004] Common porous ceramic material preparation methods such as template method and foaming method require adding organic substances such as pore formers and foaming agents to ceramic powder or slurry. These organic substances are prone to residual byproducts after sintering, making them difficult to use in mass production. In addition, the above methods still have many problems in regulating the porosity and pore size of ceramics. Therefore, it is of great significance to develop a preparation method for porous lithium ceramic tritium breeder.

[0005] In the International Journal of Hydrogen Energy (Chen R, Yang M, Shi Y, et al. Low-temperature fabrication of Li2O porous ceramic pebbles by two-stage support decomposition. International Journal of Hydrogen Energy, 2019, 44 (36): 20249-20256.), the xLi2CO3-yLiNO3 precursor green body was sintered to successfully prepare a porous Li2O ceramic with an open porosity of 29.7% and an average crushing load of 17.3N. The formation of its pore structure is attributed to the CO2 and NO2 gases produced by the decomposition of Li2CO3 and LiNO3. Although this method avoids the use of organic matter, Li2CO3 and LiNO3 are difficult to completely decompose, and the residual impurities will affect the tritium release behavior and physical and chemical properties of tritium breeding materials. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing porous lithium titanate ceramic spheres based on nanowire construction, which utilizes the characteristics of lithium titanate nanowires to construct a porous structure, and controls the porosity and pore size by controlling the sintering process, thereby avoiding the use of organic pore formers or other additives; at the same time, the structure of the nanowires overlapping each other can also ensure that the ceramics still maintain good compressive strength at high porosity.

[0007] The technical solution adopted by the present invention is a method for preparing porous lithium titanate ceramic spheres constructed based on nanowires, which is specifically implemented according to the following steps:

[0008] Step 1, preparing α-lithium titanate nanowires by a hydrothermal method;

[0009] Step 2, preparing lithium ceramic microsphere green body;

[0010] Step 3: Prepare porous β-lithium titanate ceramic spheres.

[0011] The present invention is also characterized in that:

[0012] The step 1 is specifically implemented according to the following steps:

[0013] Step 1.1, dissolving sodium hydroxide in deionized water to obtain a NaOH solution with a concentration of 8 to 12 mol / L;

[0014] Step 1.2, adding P25 titanium oxide powder to the NaOH solution obtained in step 1.1 and stirring evenly, then transferring to a stainless steel reactor lined with polytetrafluoroethylene and keeping at 180-200° C. for 12-24 hours, cooling to room temperature to 50° C. to obtain a hydrothermal product;

[0015] Step 1.3, centrifuging the hydrothermal product obtained in step 1.2 at a speed of 4000-6000 rpm / min to collect the precipitated product;

[0016] Step 1.4, using dilute hydrochloric acid with a concentration of 0.1-0.2 mol / L to acid-wash the precipitate obtained in step 1.3 for 3-4 times, then washing with deionized water until the pH is 7, and then rinsing once with anhydrous ethanol to reduce powder agglomeration;

[0017] Step 1.5, the product obtained in step 1.4 is fully dried, then ground, and calcined at 500-600° C. to obtain a powder composed of a TiO2-(B) phase and anatase TiO2 phase, and the obtained powder is dispersed in anhydrous ethanol to obtain a suspension;

[0018] Step 1.6, adding 0.5-2 mol / L lithium hydroxide solution to the suspension obtained in step 1.5, stirring and mixing, and then transferring to a stainless steel reactor lined with polytetrafluoroethylene, keeping the temperature at 150-180°C for 12-24h, cooling to room temperature-50°C to obtain a hydrothermal product, drying it, and grinding the dried product to obtain α-lithium titanate nanowire powder.

[0019] Step 2 is implemented as follows:

[0020] Step 2.1, preparing a 20 vol% ethylene glycol solution, and then adding the α-lithium titanate nanowire powder obtained in step 1.6 to prepare a slurry with a solid content of 45-55 wt%;

[0021] Step 2.2: drip the slurry obtained in step 2.1 into liquid nitrogen to form small balls, and finally take the small balls out of the liquid nitrogen and dry them to obtain lithium ceramic microsphere green bodies.

[0022] In step 2.2, the slurry is dripped into the liquid nitrogen at a rate of 10 to 20 drops per minute.

[0023] In step 2.2, the pellets are taken out from the liquid nitrogen and dried by placing them on filter paper to air dry and then transferring them to a constant temperature forced air drying oven at 70°C to 80°C for 12 to 24 hours.

[0024] Step 3 is implemented as follows:

[0025] The lithium ceramic microsphere green body obtained in step 2 is sintered at 750-950° C. for 2-6 hours, and then cooled to room temperature after sintering to obtain porous β-lithium titanate ceramic microspheres.

[0026] The beneficial effect of the present invention is that the method for preparing porous lithium titanate ceramic spheres based on nanowire construction, that is, drawing on the "bird's nest" structure, using synthesized α-lithium titanate nanowire powder, sintering to obtain pore-rich lithium titanate ceramics, avoiding the use of organic substances such as pore formers and foaming agents, is a green and environmentally friendly method. By controlling the sintering temperature, the porosity and pore size can be controlled, and the pores of the prepared ceramics are connected open-cell structures. Since a mutual overlapping structure is formed between the nanowires during the sintering process, the ceramics still have a certain compressive strength even at high porosity, which alleviates the problem of rapid degradation of ceramic strength caused by high porosity to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD patterns of porous lithium titanate ceramic microspheres prepared in Example 1-3;

[0028] Figure 2 This is a cross-sectional SEM photograph of the porous lithium titanate ceramic microspheres prepared in Example 1;

[0029] Figure 3 This is a cross-sectional SEM photograph of the porous lithium titanate ceramic microspheres prepared in Example 2;

[0030] Figure 4 This is a cross-sectional SEM photograph of the porous lithium titanate ceramic microspheres prepared in Example 3. DETAILED DESCRIPTION

[0031] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] The present invention draws on the design of the "Bird's Nest" to synthesize lithium titanate powder with nanowire morphology and then obtain lithium titanate ceramics with a porous structure through sintering. That is, the porous structure is constructed by using the characteristics of lithium titanate nanowires themselves. The porosity and pore size are regulated by controlling the sintering process, avoiding the use of organic pore formers or other additives; at the same time, the structure of the nanowires overlapping each other can also ensure that the ceramics still maintain good compressive strength at high porosity.

[0033] Based on the above concept, the specific process flow of the present invention is: first, titanium oxide nanowires synthesized by hydrothermal method are used as templates, and then α-lithium titanate nanowires are synthesized with lithium hydroxide in a hydrothermal environment, and then spherical ceramic green bodies are obtained by wet molding, and finally sintering is performed to prepare porous β-lithium titanate ceramic spheres.

[0034] The preparation method of porous lithium titanate ceramic spheres based on nanowires is specifically implemented according to the following steps:

[0035] Step 1, preparing α-lithium titanate nanowires by a hydrothermal method;

[0036] Step 1 is implemented as follows:

[0037] Step 1.1, dissolving sodium hydroxide in deionized water to obtain a NaOH solution with a concentration of 8 to 12 mol / L;

[0038] Step 1.2, adding P25 titanium oxide powder to the NaOH solution obtained in step 1.1 and stirring evenly, then transferring to a stainless steel reactor lined with polytetrafluoroethylene and keeping at 180-200° C. for 12-24 hours, cooling to room temperature to 50° C. to obtain a hydrothermal product;

[0039] Step 1.3, centrifuging the hydrothermal product obtained in step 1.2 at a speed of 4000-6000 rpm / min using a centrifuge to collect the precipitated product;

[0040] Step 1.4, using dilute hydrochloric acid with a concentration of 0.1-0.2 mol / L to acid-wash the precipitate obtained in step 1.3 for 3-4 times, then washing with deionized water until the pH is 7, and then rinsing once with anhydrous ethanol to reduce powder agglomeration;

[0041] Step 1.5, the product obtained in step 1.4 is fully dried, then ground into powder and placed in an alumina crucible, transferred into a muffle furnace and calcined at 500-600° C. to obtain a powder composed of a TiO2-(B) phase and anatase TiO2 phase, and the obtained powder is dispersed in anhydrous ethanol to obtain a suspension;

[0042] Step 1.6, adding 0.5-2 mol / L lithium hydroxide solution to the suspension obtained in step 1.5, stirring and mixing, and then transferring it to a stainless steel reactor lined with polytetrafluoroethylene, and placing it in a forced air drying oven at 150-180°C for 12-24 hours, cooling it to room temperature-50°C to obtain a hydrothermal product, and grinding the dried product to obtain α-lithium titanate nanowire powder.

[0043] Step 2, preparing lithium ceramic microsphere green body;

[0044] Step 2 is implemented as follows:

[0045] Step 2.1, preparing a 20 vol% ethylene glycol solution, and then adding the α-lithium titanate nanowire powder obtained in step 1.6 to prepare a slurry with a solid content of 45-55 wt%;

[0046] Step 2.2: drip the slurry obtained in step 2.1 into liquid nitrogen to form small balls, and finally take the small balls out of the liquid nitrogen and dry them to obtain lithium ceramic microsphere green bodies.

[0047] In step 2.2, the slurry is dripped into the liquid nitrogen at a rate of 10 to 20 drops per minute.

[0048] In step 2.2, the pellets are taken out from the liquid nitrogen and dried by placing them on filter paper to air dry and then transferring them to a constant temperature forced air drying oven at 70°C to 80°C for 12 to 24 hours.

[0049] Step 3: Prepare porous β-lithium titanate ceramic spheres.

[0050] Step 3 is implemented as follows:

[0051] The lithium ceramic microsphere green body obtained in step 2 is sintered at 750-950°C for 2-6h, and then cooled to room temperature after sintering to obtain porous β-lithium titanate ceramic spheres. During the sintering process, the nanowires of the lithium ceramic microsphere green body overlap each other, and the contact points are gradually sintered to form a "bird's nest" structure, ensuring that the prepared ceramic still has good mechanical strength at high porosity, and to a certain extent alleviates the problem of rapid degradation of ceramic strength caused by high porosity. At the same time, the porosity and pore size can be regulated by controlling the sintering temperature and sintering time. The present invention avoids the use of organic substances such as pore formers and foaming agents, and is a green and environmentally friendly method for preparing porous ceramics.

[0052] Example 1

[0053] (1) Preparation of α-lithium titanate nanowire powder

[0054] 1g P25 titanium oxide powder was added to a NaOH solution with a concentration of 8mol / L, and mechanically stirred for 15min to obtain a uniform mixed solution. The solution was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and hydrothermally reacted at 180℃ for 12h. After cooling, the precipitate was collected by centrifugation at a speed of 4000rpm / min using a centrifuge. The precipitate was then added to a 0.1mol dilute hydrochloric acid solution for three to four repeated centrifugal acid washings. After that, the product was repeatedly centrifuged and washed with deionized water until the pH was 7. The precipitate was added to anhydrous ethanol solution and centrifuged and washed once to prevent powder agglomeration. After washing, the centrifuged product was dried at 70℃ for 12h. The dried product was ground into fine powder using an agate mortar, transferred to an alumina crucible, placed in a muffle furnace and calcined at 500℃ for 2h to obtain a powder composed of TiO2-(B) phase and anatase TiO2 phase.

[0055] The TiO2-(B) / anatase TiO2 powder prepared above and LiOH·H2O were weighed in a molar ratio of 1:2. LiOH·H2O was dispersed in deionized water and stirred for 15 minutes until the solution was clear to obtain a lithium hydroxide solution with a concentration of 0.5 mol / L; TiO2-(B) / anatase TiO2 powder was added to anhydrous ethanol for mixing, and then the two solutions were mixed and stirred on a magnetic stirrer for 15 minutes until the solution was mixed evenly, and the volume ratio of anhydrous ethanol to deionized water was maintained at 1:1. The solution was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and placed at 150°C for a hydrothermal reaction for 12 hours. After the reactor was cooled, the solution was transferred to a glass culture dish and dried at 70°C. After drying, the dried product was ground using an agate mortar to obtain α-lithium titanate nanowire powder.

[0056] (2) Preparation of lithium ceramic microsphere green body

[0057] The α-lithium titanate nanowire powder was mixed with a homemade 20 vol% ethylene glycol aqueous solution in a certain ratio to prepare a slurry with a solid content of 45 wt%. The slurry was then dripped into liquid nitrogen at a rate of 10 drops / minute to form small balls, which were then taken out of the liquid nitrogen and placed on filter paper for air drying, and then transferred to a 70°C constant temperature forced air drying oven for drying for 12 hours to obtain a spherical α-lithium titanate ceramic green body;

[0058] (3) Preparation of porous β-lithium titanate ceramic spheres

[0059] The spherical lithium ceramic blank obtained in step (2) is sintered in a sintering furnace at 750° C. for 2 hours. After the sintering is completed, the spherical lithium ceramic blank is cooled to room temperature in the furnace to obtain porous β-lithium titanate ceramic spheres.

[0060] The XRD spectrum of the lithium titanate ceramic spheres prepared in Example 1 is as follows: Figure 3 (Testing after grinding the ceramic balls), it can be seen that its main component is β-lithium titanate; the porosity of the prepared β-lithium titanate ceramic balls is 30.9%, and the average crushing strength is 6.61N; the SEM photo of its cross section is as follows Figure 4 .

[0061] Example 2

[0062] (1) Preparation of α-lithium titanate nanowire powder

[0063] 1g P25 titanium oxide powder was added to a NaOH solution with a concentration of 12mol / L, and mechanically stirred for 30min to obtain a uniform mixed solution. The solution was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and hydrothermally reacted at 200℃ for 24h. After cooling, the precipitate was collected by centrifugation at a speed of 6000rpm / min using a centrifuge, and then the precipitate was added to a 0.2mol dilute hydrochloric acid solution for three to four repeated centrifugal acid washings. After that, the product was repeatedly centrifuged and washed with deionized water until the pH was 7, and then the precipitate was added to anhydrous ethanol solution for centrifugal washing once to prevent powder agglomeration. After washing, the centrifuged product was dried at 80℃ for 24h. After the dried product was ground into fine powder using an agate mortar, it was transferred to an alumina crucible, placed in a muffle furnace and calcined at 600℃ for 4h to obtain a powder composed of TiO2-(B) phase and anatase TiO2 phase.

[0064] The TiO2-(B) / anatase TiO2 powder prepared above and LiOH·H2O were weighed in a molar ratio of 1:2. LiOH·H2O was dispersed in deionized water and stirred for 30 minutes until the solution was clear to obtain a lithium hydroxide solution with a concentration of 2 mol / L; TiO2-(B) / anatase TiO2 powder was added to anhydrous ethanol for mixing, and then the two solutions were mixed and stirred on a magnetic stirrer for 30 minutes until the solution was mixed evenly, and the volume ratio of anhydrous ethanol to deionized water was maintained at 1:1. The solution was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and placed at 180°C for a hydrothermal reaction for 24 hours. After the reactor was cooled, the solution was transferred to a glass culture dish and dried at 80°C. After drying, the dried product was ground using an agate mortar to obtain α-lithium titanate nanowire powder.

[0065] (2) Preparation of lithium ceramic microsphere green body

[0066] The α-lithium titanate nanowire powder was mixed with a homemade 20 vol% ethylene glycol aqueous solution in a certain ratio to prepare a slurry with a solid content of 55 wt%. The slurry was then dripped into liquid nitrogen at a rate of 20 drops / minute to form small balls, which were then taken out of the liquid nitrogen and placed on filter paper for air drying, and then transferred to a constant temperature blast drying oven at 80°C for drying for 24 hours to obtain a spherical α-lithium titanate ceramic green body;

[0067] (3) Preparation of porous β-lithium titanate ceramic spheres

[0068] The spherical lithium ceramic blank obtained in step (2) is sintered in a sintering furnace at 850° C. for 4 hours. After the sintering is completed, the spherical lithium ceramic blank is cooled to room temperature in the furnace to obtain porous β-lithium titanate ceramic spheres.

[0069] The XRD spectrum of the lithium titanate ceramic spheres prepared in Example 2 is as follows: Figure 3 (Testing after grinding the ceramic balls), it can be seen that its main component is β-lithium titanate; the porosity of the prepared β-lithium titanate ceramic balls is 35.2%, and the average crushing strength is 9.06N; the SEM photo of its cross section is as follows Figure 3 .

[0070] Example 3

[0071] (1) Preparation of α-lithium titanate nanowire powder

[0072] 1g P25 titanium oxide powder was added to a 10mol / L NaOH solution, mechanically stirred for 30min to obtain a uniform mixed solution, and then the solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene for hydrothermal reaction at 200℃ for 24h. After cooling, the precipitate was collected by centrifugation at a speed of 5000rpm / min, and then the precipitate was added to a 0.2mol dilute hydrochloric acid solution for three to four repeated centrifugal acid washings, and then the precipitate was repeatedly centrifuged and washed with deionized water until the pH was 7, and then the precipitate was added to anhydrous ethanol solution for centrifugal washing once to prevent powder agglomeration. After washing, the centrifuged product was dried at 80℃ for 12h. After the dried product was ground into fine powder using an agate mortar, it was transferred to an alumina crucible, placed in a muffle furnace and calcined at 550℃ for 2h to obtain a powder composed of TiO2-(B) phase and anatase TiO2 phase.

[0073] The TiO2-(B) / anatase TiO2 powder prepared above and LiOH·H2O were weighed in a molar ratio of 1:2. LiOH·H2O was dispersed in deionized water and stirred for 15 minutes until the solution was clear to obtain a lithium hydroxide solution with a concentration of 1 mol / L; TiO2-(B) / anatase TiO2 powder was added to anhydrous ethanol for mixing, and then the two solutions were mixed and stirred on a magnetic stirrer for 15 minutes until the solution was mixed evenly, and the volume ratio of anhydrous ethanol to deionized water was maintained at 1:1. The solution was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and placed at 165°C for a hydrothermal reaction for 12 to 24 hours. After the reactor was cooled, the solution was transferred to a glass culture dish and dried at 80°C. After drying, the dried product was ground using an agate mortar to obtain α-lithium titanate nanowire powder.

[0074] (2) Preparation of lithium ceramic microsphere green body

[0075] The α-lithium titanate nanowire powder was mixed with a homemade 20 vol% ethylene glycol aqueous solution in a certain ratio to prepare a slurry with a solid content of 50 wt%. The slurry was then dripped into liquid nitrogen at a rate of 20 drops / minute to form small balls, which were then taken out of the liquid nitrogen and placed on filter paper for air drying, and then transferred to a constant temperature blast drying oven at 80°C for drying for 24 hours to obtain a spherical α-lithium titanate ceramic green body;

[0076] (3) Preparation of porous β-lithium titanate ceramic spheres

[0077] The spherical lithium ceramic blank obtained in step (2) is sintered in a sintering furnace at 950° C. for 4 hours. After the sintering is completed, the spherical lithium ceramic blank is cooled to room temperature in the furnace to obtain porous β-lithium titanate ceramic spheres.

[0078] The XRD spectrum of the lithium titanate ceramic spheres prepared in Example 3 is as follows: Figure 3 (Testing after grinding the ceramic balls), it can be seen that its main component is β-lithium titanate; the porosity of the prepared β-lithium titanate ceramic balls is 29.4%, and the average crushing strength is 15.9N; the SEM photo of its cross section is as follows Figure 4 .

[0079] contrast Figure 2-4 It can be clearly seen that the prepared lithium titanate ceramic has a loose porous structure, and its pores are formed by nanowires. The pores are interconnected, which is conducive to the rapid diffusion and migration of tritium inside the ceramic. In addition, the porosity and pore size of lithium titanate ceramics can be regulated by controlling the sintering temperature or sintering time.

[0080] Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. For example, porous lithium silicate ceramics are constructed by lithium silicate nanowires, porous lithium zirconate ceramics are constructed by lithium zirconate nanowires, etc.

Claims

1. A method for preparing porous lithium titanate ceramic spheres based on nanowires, characterized in that: Follow the steps below to implement it: Step 1, preparing α-lithium titanate nanowires by a hydrothermal method; The step 1 is specifically implemented according to the following steps: Step 1.1, dissolving sodium hydroxide in deionized water to obtain a NaOH solution with a concentration of 8 to 12 mol / L; Step 1.2, adding P25 titanium oxide powder to the NaOH solution obtained in step 1.1 and stirring evenly, then transferring to a stainless steel reactor lined with polytetrafluoroethylene and keeping at 180-200° C. for 12-24 hours, cooling to room temperature to 50° C. to obtain a hydrothermal product; Step 1.3, centrifuging the hydrothermal product obtained in step 1.2 at a speed of 4000-6000 rpm / min to collect the precipitated product; Step 1.4, using dilute hydrochloric acid with a concentration of 0.1-0.2 mol / L to acid-wash the precipitate obtained in step 1.3 for 3-4 times, then washing with deionized water until the pH is 7, and then rinsing once with anhydrous ethanol to reduce powder agglomeration; Step 1.5, the product obtained in step 1.4 is fully dried, then ground, and calcined at 500-600° C. to obtain a powder composed of a TiO2-(B) phase and anatase TiO2 phase, and the obtained powder is dispersed in anhydrous ethanol to obtain a suspension; Step 1.6, adding 0.5-2 mol / L lithium hydroxide solution to the suspension obtained in step 1.5, stirring and mixing, and then transferring to a stainless steel reactor lined with polytetrafluoroethylene, keeping the temperature at 150-180° C. for 12-24 hours, cooling to room temperature-50° C. to obtain a hydrothermal product, drying it, and grinding the dried product to obtain α-lithium titanate nanowire powder; Step 2, preparing lithium ceramic microsphere green body; The step 2 is specifically implemented according to the following steps: Step 2.1, preparing a 20 vol% ethylene glycol solution, and then adding the α-lithium titanate nanowire powder obtained in step 1.6 to prepare a slurry with a solid content of 45-55 wt%; Step 2.2, dropping the slurry obtained in step 2.1 into liquid nitrogen to form small balls, and finally taking the small balls out of the liquid nitrogen and drying them to obtain lithium ceramic microsphere green bodies; In the step 2.2, the slurry is dripped into the liquid nitrogen at a rate of 10 to 20 drops per minute; In the step 2.2, the pellets are taken out from the liquid nitrogen and dried by placing the pellets on filter paper for air drying and then transferring them to a constant temperature blast drying oven at 70° C. to 80° C. for 12 to 24 hours; Step 3, preparing porous structure β-lithium titanate ceramic beads; The step 3 is specifically implemented according to the following steps: The lithium ceramic microsphere green body obtained in step 2 is sintered at 750-950° C. for 2-6 hours, and then cooled to room temperature after sintering to obtain porous β-lithium titanate ceramic microspheres.

Citation Information

Patent Citations

  • Tritium proliferation agent lithium titanate ceramic pellet with high degree of sphericity and nano structure and preparation method of tritium proliferation agent lithium titanate ceramic pellet

    CN108911735A

  • Preparation method and application of hydroxyapatite nanowire sintered porous ceramic beads

    CN113416069A

  • Method for Manufacturing Lithium Titanate Heterogeneous Nano Structures and Anode Active Materials Comprising the Same

    KR1020120022259A